Sport and physical culture in occupied France : authoritarianism, agency, and everyday life - Rathbone, Keith 2022- (Studies in modern French and francophone history, 2022)
Sport and physical culture in Occupied France examines the Vichy state's attempts to promote physical education and sports in order to rejuvenate French men and women during the Occupation. Through this cultural lens, it illuminates the central paradox of state power during the Vichy Regime. The state organised a centralised physical cultural programme meant to control and discipline French men and women. However, these activities instead empowered individuals and sporting associations to create spaces for individual expression, protect entrenched business enterprises, preserve republican institutions and organise sites for mutual aid and assistance. Based on extensive archival research, this innovative, multi-city analysis demonstrates how French sporting federations, associations and athletes appropriated Vichy's physical education directives to reshape the ideology of the state and serve their own local agendas